COMPARISON OF EARLY NEONATAL OUTCOMES FOR ASYMMETRICAL IUGR WITH NORMAL AND ABNORMAL UMBILICAL ARTERY WAVEFORMS - Noor, Lubna; Arshad, Humaira; Tariq, Humaira; Afsheen, Afeera (Pakistan Armed Forces Medical Journal, 2020)
Objective: To compare early neonatal outcome of asymmetrical IUGR fetuses with normal and abnormal umbilical artery Doppler waveforms.Study Design: Cohort study.Place and Duration of Study: Department of Obstetrics and Gynecology, Military Hospital, Rawalpindi from Jul 2010 to Dec 2010.Material and Methods: Total of 66 patients with normal and abnormal Doppler umbilical artery waveforms with asymmetrical IUGR were included in the study. The study group consisted of 33 patients having asymmetrical IUGR with normal umbilical artery Doppler RI < 0.65 (Group 1) and 33 with abnormal umbilical artery Doppler RI> 0.65 (Group 2) These underwent serial Doppler umbilical artery study. Neonatal outcomes measured in terms of APGAR score, Birth weight, admission to NICU and number of still births.Result: The mean gestational age at delivery of group 1 was 36 ± 2.0 weeks and mean gestational age of group 2 was 33 ± 2.9 weeks (p-value=0.002) The Birth weight in group 1 was 2078 ± 408 grams and group 2 was 1642 ± 426 grams (p-value=0.000). The APGAR score of neonate at 5 minutes in group 1 ranged 7.6 ± 2.2 and that in group 2 with abnormal Doppler waveforms ranged 5 ± 2.3. These differences are statistically significant. Neonates with APGAR of less than 7 were admitted to NICU. In group 1, 24 neonates were having APGAR score of 7 or more and were not admitted to NICU while in group 2, 24 were admitted to NICU as the APGAR score were less than 7. Chi-square test was used and the difference was found significant. Still births in both the groups were compared. In group 1 there was only one still birth whereas there were 4 still births in group 2 p-value=0.355. There is no significance differences (p>0.05).Conclusion: Abnormal umbilical artery Doppler is a better predictor of neonatal outcome in terms of APGAR score, Birth weight, NICU admission and probability of still births than normal Doppler study.